Comparison between surgical fusion and the growing-rod technique for early-onset neurofibromatosis type-1 dystrophic scoliosis - Cai, Siyi; Cui, Liqiang; Qiu, Guixing; Shen, Jianxiong; Zhang, Jianguo (BMC musculoskeletal disorders, 2020)
Spinal deformities constitute one of the most common types of manifestations of neurofibromatosis type-1 (NF-1), which can lead to either dystrophic or non-dystrophic early-onset scoliosis (EOS). Surgical treatment for EOS with NF-1 is challenging, and the outcomes have rarely been reported. The anterior-posterior procedure is widely used, but posterior-only fusion is theoretically easier and safer to perform. Is it possible that a new surgery that accommodates growth is a better choice? A direct comparison between posterior fusion and growth-friendly surgery in terms of surgical outcomes has not yet been conducted in dystrophic EOS with NF-1 patients. Baseline information was extracted from the NF-1 database at our institute with approval from the local ethics committee. All enrolled patients were diagnosed with NF-1. Clinical and radiographic data were recorded preoperatively, after the initial surgery, and at the final follow-up. Implant-related, alignment, neurological complication and unplanned revision surgery data were recorded. We compared the outcomes of these two groups in terms of curve correction, growth parameters, complications and unplanned revision surgeries. There were eight patients in the PF group and eight patients in the GR group, with a mean follow-up of 51.0 ± 17.5 months. The main curve size was similar (PF 67.38° ± 17.43° versus GR 75.1° ± 26.43°, P = 0.501), and there were no significant differences in the initial surgery correction rate or the rate of correction. However, the patients in the GR group exhibited more T1-S1 growth during the follow-up overall and per year than did those in the PF group. The operative time was significantly longer for the PF group than for the GR group (PF, 4.39 ± 1.38 vs. GR, 3.00 ± 0.42 h; p = 0.008). Significantly fewer segments were involved in the PF group (8.25 ± 3.20) than in the GR group (13.00 ± 1.60). For the initial treatment of dystrophic EOS in patients with NF-1, the GR technique is possibly a more appropriate treatment than is the PF technique in terms of trunk growth. However, the repeated procedures required for GR may be a considerable disadvantage. More studies with direct measurement of pulmonary function must be conducted to determine the effect of GR on pulmonary development. More studies with larger sample sizes and longer follow-up periods are needed to fully assess the treatment strategies.